2009
DOI: 10.5194/angeo-27-3737-2009
|View full text |Cite
|
Sign up to set email alerts
|

Statistical characteristics of AGW wave packet propagation in the lower atmosphere observed by the MU radar

Abstract: Abstract. We study the horizontal structure of the atmospheric gravity waves (AGW) in the height ranges between 6 and 22 km observed using the MU radar at Shigaraki in Japan, during a 3 day period in January and a 4 day period in August 1988. The data were divided by double Fourier transformation into a data set of upward moving waves and a data set of downward moving waves for independent analysis. The phase and group velocity tracing technique was applied to measure the vertical group and phase velocity as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 20 publications
4
13
0
Order By: Relevance
“…So, both case studies (Sects. 3.3.1 and 3.4) revealed that the results of wave packet analysis were closely associated with the high frequency part of the wave spectrum in Table 2c, because high frequency waves had better relative frequency resolution ω ω than low frequency waves (Kuo et al, 2003(Kuo et al, , 2009). The results of hodograph analysis associated with these 20 wave packets were shown by a green dot in Fig.…”
Section: Superposition Of Five Waves Propagating In Same Direction Vementioning
confidence: 96%
See 3 more Smart Citations
“…So, both case studies (Sects. 3.3.1 and 3.4) revealed that the results of wave packet analysis were closely associated with the high frequency part of the wave spectrum in Table 2c, because high frequency waves had better relative frequency resolution ω ω than low frequency waves (Kuo et al, 2003(Kuo et al, , 2009). The results of hodograph analysis associated with these 20 wave packets were shown by a green dot in Fig.…”
Section: Superposition Of Five Waves Propagating In Same Direction Vementioning
confidence: 96%
“…Then the most probable characteristic intrinsic frequency, horizontal wavelength and azimuth of each wave packet can be found by fitting the dispersion equation and its related formula for vertical group velocity (Kuo et al, 2009). In this paper, we shall compare the merit and demerit of each method and try to find a composite procedure for obtaining the most probable propagation parameters of AGWs.…”
Section: H Y Lue and F S Kuo: Comparative Studies Of Methods Of Omentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the traditional hodograph analysis in fact can only be applied to study low-frequency GWs. Observational studies on lower-atmospheric medium-and high-frequency GWs (MHGWs) are mainly from only radiosonde at a tropical station (Leena et al, 2012b) and few radar observations at several limited sites (Dutta et al, 2009;Kuo et al, 2009, Leena et al, 2012b. Then, considering the long-term accumulations and extensive land distribution of radiosonde observations, in order to further understand the MHGWs in the lower atmosphere we need a feasible method to extract MHGW parameters from more radiosonde observations.…”
Section: S D Zhang Et Al: Spatial and Seasonal Variability Of Medimentioning
confidence: 99%